2020
DOI: 10.1136/bmjopen-2019-033096
|View full text |Cite
|
Sign up to set email alerts
|

Enablers and barriers to the implementation of socially assistive humanoid robots in health and social care: a systematic review

Abstract: ObjectivesSocially assistive humanoid robots are considered a promising technology to tackle the challenges in health and social care posed by the growth of the ageing population. The purpose of our study was to explore the current evidence on barriers and enablers for the implementation of humanoid robots in health and social care.DesignSystematic review of studies entailing hands-on interactions with a humanoid robot.SettingFrom April 2018 to June 2018, databases were searched using a combination of the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 52 publications
(225 reference statements)
3
97
0
4
Order By: Relevance
“…The interactive and dynamic features of social robots, and their ability to understand and respond to human emotion, make them candidate solutions for application domains that require social engagement and comfort. In healthcare, social robots are being investigated and implemented as tools to assist patients by means of emotional support across the lifespan, from pediatric populations ( Kabacińska et al., 2020 ) to older adults ( Broekens et al., 2009 ; Robinson et al., 2014 ; Prescott and Caleb-Solly, 2017 ; Pu et al., 2018 ; Papadopoulos et al., 2020 ). In education, social robots are being used as tutors or co-learners to promote cognitive and affective outcomes including social skills development ( Belpaeme et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The interactive and dynamic features of social robots, and their ability to understand and respond to human emotion, make them candidate solutions for application domains that require social engagement and comfort. In healthcare, social robots are being investigated and implemented as tools to assist patients by means of emotional support across the lifespan, from pediatric populations ( Kabacińska et al., 2020 ) to older adults ( Broekens et al., 2009 ; Robinson et al., 2014 ; Prescott and Caleb-Solly, 2017 ; Pu et al., 2018 ; Papadopoulos et al., 2020 ). In education, social robots are being used as tutors or co-learners to promote cognitive and affective outcomes including social skills development ( Belpaeme et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The recent systematic review by Papadopoulos et al [ 15 ] has provided important insights relating to the implementation of SAHRs. Our review differs in that it encompasses a broader scope to allow inquiry into the implementation of all variants of social robots.…”
Section: Rationalementioning
confidence: 99%
“…Despite positive findings with regards to the effects of social robots for older adults, little is known about how to ensure that these interventions are implemented in practice. Papadopoulos and colleagues conducted a systematic review of twelve articles to identify enablers and barriers to the implementation of socially assistive humanoid robots (SAHR) in health and social care [ 15 ]. The authors found that facilitators include participants’ enjoyment, intuitiveness and ease of use of the SAHR, personalisation of SAHR services to users’ needs, as well as familiarity towards the SAHR.…”
Section: Introductionmentioning
confidence: 99%
“…This taxonomy consists of eight constructs, which includes: acceptability, adoption, appropriateness, feasibility, delity, implementation cost, penetration and sustainability. Some of these concepts have been used in studies to describe implementation of SAHRs (15). Therefore, use of these concepts as part of the search strategy will likely yield relevant results and ensure thoroughness of the searches.…”
Section: Search Strategymentioning
confidence: 99%
“…Despite positive ndings with regards to the effects of social robots for older adults, little is known about how to ensure that these interventions are implemented in practice. Papadopoulos and colleagues conducted a systematic review of twelve articles to identify enablers and barriers to the implementation of socially assistive humanoid robots (SAHR) in health and social care (15). The authors found that facilitators include participants' enjoyment, intuitiveness and ease of use of the SAHR, personalisation of SAHR services to users' needs, as well as familiarity towards the SAHR.…”
Section: Introductionmentioning
confidence: 99%